Românii din Ucraina: de la autoidentificare la păstrarea și promovarea valorilor naționale - (:unkn) unknown (Mesager Bucovinean, 2024)
In the case of the Romanian language spoken in the Romanian communities in Ukraine, the last decades represented a difficult period, characterized by a pronounced socio-political instability, which led to major changes in its functional status. For the Romanian ethnic groups from regions like Chernivtsi, Odessa or Transcarpathia, there is a very close connection between language and national identity. The idea of nation is not associated in these geographical spaces with the idea of state institutions, but with the idea of language, with cultural values, as well as with the historical past. Feeling this acute need to assert their identity, the members of the Romanian communities attach much greater importance to the manifestation of national identity through cultural-artistic activities, promoting the idea of resistance through culture much more intensely. The social-political changes that have taken place in Ukraine in recent years have influenced and will continue to significantly influence the situation of minorities. However, it is equally obvious that these changes created a rather complicated social-political context, less favorable to asserting the linguistic identity of persons belonging to national minorities, including on the representatives of the Romanian community. In Ukraine, in the areas inhabited by Romanians, at least three languages are spoken: Romanian, Russian and Ukrainian. Of course, not all speakers are equally fluent in the three languages, most often seeing a certain „specialization”: Romanian predominates in the family environment, while Russian and Ukrainian are more commonly used in the professional environment. In recent years, at the legislative level, a series of measures have been taken whose main objective is to strengthen the positions of the Ukrainian language as a state language, it being obvious that there are still a large number of speakers, ethnic Ukrainians, who prefer to communicate in Russian and not in Ukrainian.